Evaluation of the effect of GSK-3β on liver cancer based on the PI3K/AKT pathway - Guo, Jiageng; Jiang, Xinya; Lian, Jing; Li, Huaying; Zhang, Fan; Xie, Jinling; Deng, Jiagang; Hou, Xiaotao; Du, Zhengcai; Hao, Erwei (Frontiers in Cell and Developmental Biology, 2024)
The PI3K/AKT/GSK-3β signaling pathway plays a pivotal role in numerous physiological and pathological processes, including cell proliferation, apoptosis, differentiation, and metabolic regulation.Aberrant activation of the PI3K/AKT pathway is intricately linked to development of tumor. GSK-3β, belonging to the serine/threonine protein kinase family, is crucial in the pathogenesis of liver cancer. As a key rate-limiting enzyme in the glucose metabolism pathway, GSK-3β significantly impacts the growth, proliferation, metastasis, and apoptosis of liver cancer cells. It is also implicated in chemotherapy resistance.Elevated expression of GSK-3β diminishes the sensitivity of liver cancer cells to chemotherapeutic agents, thereby playing a substantial role in the